Analysis of the Efficiency of Local Government Spending in Poverty Alleviation and Unemployment Reduction in West Java Province - Jormarito Elizabet Siahaan; Roosemarina Anggraini Rambe (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to measure the efficiency of local government spending in West Java Province during the COVID-19 pandemic in 2020. The inputs used are economic spending, education, health, public facilities, and infrastructure. The outputs used are poverty rate and unemployment rate. The analysis method used is Data Envelopment Analysis (DEA) with an output-oriented model based on variable Return to Scale (VRS) approach. The results showed that 19 local governments were relatively efficient; which consists of 10 districts and 9 cities. The ten efficient districts are Bogor, Bandung, Garut, Tasikmalaya, Ciamis, Sumedang, Indramayu, Purwakarta, Bekasi, Pangandaran. While the nine efficient cities are Bogor, Sukabumi, Cimahi, Bandung, Cirebon, Bekasi, Depok, Tasikmalaya, Banjar.